1997
DOI: 10.1080/09540129750124975
|View full text |Cite
|
Sign up to set email alerts
|

Widely varying HIV prevalence and risk behaviours among the ethnic minority peoples of northern Thailand

Abstract: We compared HIV prevalence, risk behaviours, and social and sexual norms among nine ethnic minority (Hilltribe) groups in northern Thailand. Communities were selected on the basis of size, ethnicity, development level and geography. Subjects (15-45 years) were stratified by gender and selected by household using two-stage randomization. Forty volunteers were identified in each of 27 villages. Participation was voluntary and informed consent was obtained. HIV infection status was determined using ELISA and West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…Data are also needed on the effectiveness of VCT in reducing risk behaviors and HIV incidence in those who seek testing and the effectiveness of the referral system in caring for and supporting those who test positive. Whether rapid tests, such as ORA-QUICK, or noninvasive methods, such as those using urine or saliva testing, would increase the acceptability of HIV testing or improve notification is worth evaluating (Hilton et al, 2002;Beyrer et al, 1997;Kassler, 1997;Nookhai et al, 2001). This research agenda is crucial for improving the effectiveness of the national HIV prevention program in Thailand.…”
Section: Discussionmentioning
confidence: 97%
“…Data are also needed on the effectiveness of VCT in reducing risk behaviors and HIV incidence in those who seek testing and the effectiveness of the referral system in caring for and supporting those who test positive. Whether rapid tests, such as ORA-QUICK, or noninvasive methods, such as those using urine or saliva testing, would increase the acceptability of HIV testing or improve notification is worth evaluating (Hilton et al, 2002;Beyrer et al, 1997;Kassler, 1997;Nookhai et al, 2001). This research agenda is crucial for improving the effectiveness of the national HIV prevention program in Thailand.…”
Section: Discussionmentioning
confidence: 97%
“…The Hmong refugees born in Thailand were on average 20-30 years younger than those born in Laos, so risk factors for acquiring HCV infection may be different between these two Hmong groups. It has been reported that injection drug use has increased among the Hmong, 39 thereby potentially contributing to the higher rate of HCV-RNA-positivity observed for the Thai Hmong. Currently, no specific policy exists for hepatitis C screening of immigrants or refugees, although CDC has recently included in its recommendations one-time screening for hepatitis C of all individuals born between 1945 and 1965.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conservative nature of the Karen sexual culture might contribute to the extremely low HIV prevalence rate (Beyrer et al, 1997), despite living close to the infection epicenter in Thailand, our findings suggest that this trend will not persist. As HIV spread readily and widely among FSWs and male clients in the Thai population within a short time in the early 1990s, especially in northern Thailand, emerging unprotected sexual contact with a FSW, and other nontraditional sexual behaviors, will allow the HIV to infiltrate these mountain-dwelling ethnic minority communities if no timely, effective preventive measures are taken.…”
Section: Discussionmentioning
confidence: 49%
“…Studies in the late 1990s compared the HIV prevalence, sexual attitudes, and behaviors of the villagers among several ethnic minorities (Beyrer et al, 1997;Omori, 1999). These studies demonstrated the presence of a major risk factor for HIV infection: contact with Thai society.…”
Section: Introductionmentioning
confidence: 99%